Evaluación de diferentes niveles de proteína en el desarrollo corporal y gastrointestinal de aves de competencia en la Hoya de Loja - Calderón Maza, Francisco Michael (2019)
In the present investigation, different levels of protein in the body and gastrointes- tinal development of competing birds in the Hoja de Loja were evaluated; for which, shed number two of the Fifth Experimental Punzara of the National University of Loja, located at 2160 m.s.n.m. Approximately three hundred competition chickens were used, 150 males and 150 females one day old were housed in groups of 30 animals (experimental unit). The experiment was developed under a design with a 2 x 2 factorial arrangement. Two diets were prepared for growth: the first diet was formulated with 3060 Kcal / Kg and 20 % of PB and the second diet was prepared with 3060 Kcal / Kg and 16 % of PB. Four programs were tested: i) feeding of 50 % females with the first diet ii) feeding of the birds 50 % male with the first diet, iii) feeding of 50 % females with the second diet, iv) feeding of the 50 % male birds with the second diet diets were supplied ad libitum. The animals were sacrificed at day 56 of age (one animal per experimental unit). The total digestive tract, proven- triculus, gizzard, small intestine, large intestine, liver and blind were weighed. The results were analyzed, with an analysis of variance, where the main sources of varia- tion were protein levels, sex and their interaction. The fiber level of 20 %, improved the productive parameters, obtaining satisfactory weights to the channel also reduced the mortality rate, compared to animals fed with 16 % fiber. In the digestive parame- ters, the animals fed with 20 % of fiber obtained greater weights, in organs such as: gizzard. Keywords: Poultry farming, competition birds, food, protein.